Можливості застосування фрактальних моделей для ідентифікації мікрокліматичних параметрів музейних приміщень - Довгалюк, Володимир Борисович; Ситницька, А. К.; Човнюк, Ю. В.; Іванов, Є. О. (КНУБА, 2019)
Для ідентифікації кліматичних параметрів музейних приміщень використовуються моделі різного типу залежно від поставлених цілей дослідження. Труднощі у виборі моделі зумовлена складністю поведінки систем формування мікроклімату у різні моменти часу, при зміні інтенсивності процесів тепломасообміну в музейних приміщеннях. На прикладі повітряної каруселі Е. Лоренца показано застосування фрактального моделювання для опису поведінки вказаних вище систем як чисельно незвідних систем. Наведено алгоритм визначення області самоподібності для досліджуваного об’єкта, що, на думку авторів, дозволяє знизити ймовірність порушення штатного режиму його роботи. Розглянуті можливості застосування фрактальних моделей для ідентифікації параметрів систем забезпечення мікроклімату музейних приміщень.Запропоновані шляхи ідентифікації складних систем із застосування фрактального формалізму, котрі можуть бути в подальшому використані для вдосконалення існуючих систем створення штучного мікроклімату в музейних приміщеннях на основі функціюваннямікроконтролерів з нечіткою логікою. To identify climatic parameters of museum premises there are models of different types depending on the goals of the research: modification of the algorithm of the microclimate control, the performance of air conditioners, the parameters of the inflow air or selection of air distribution system. The difficulty in choosing a model is due to the complexity of the behaviour of microclimate formation systems at different moments of time, with the change in the intensity of heat-mass transfer processes in museum premises. Using the example of the air merry-go-round of E. Lorenz, the use of fractal modelling is shown to describe the behaviour of the above systems as numerically invariant systems. Here is given an algorithm for determination of the region of self-similarity for the investigated object, which, according to the authors, may reduce the probability of a violation of the regular conditions of its operation. In the article there are possibilities of using fractal models for identifying the parameters of the systems of providing the microclimate in museum premises. The ways of identifying complex systems using fractal formalism are suggested, which can be further used to improve the existing systems of formation the artificial microclimate in museum premises on the basis of the operation of microcontrollers with fuzzy logic. It is established that there is a need to provide a system that promptly sends a signal about an increase in the probability of an unusual situation (excessive humidity, high temperature in the area where the paintings are located). To do this, it is necessary to determine one of the boundaries of the region of self-similarity of the air parameters when entering the air flow into the service area (the location of the exhibit), and the second boundary of the region of self-similarity at the outflow of air flow from the service area.
The Possibility of Using a Fractal Model to Identify Climatic Parameters of Museum Premises
https://doi.org/10.32347/2409-2606.2019.29.6-11
Keywords: ідентифікація; мікроклімат; музейне приміщення; карусель Лоренца; область самоподібності; 551.584:727:069